Economic aspects of youth training in industrialised countries
Two apparently unrelated force have resulted in a significant increase in interest in the role of training in a modern industrialist economy. One force is increase in umemployment and second force is the development of endigenous growth theory, with its emphasis on human capital. The analysis of the economics of training has been conducted at a number of levels but has been sharply focussed at the youth level. This is so for several reasons. First, increase in youth unemployment, second, the skills which now entrants join the labour market will have an important bearing on the likelihood of gaining employment and the nature of that employment. Third, the type of training acquired will have an important bea
Keywords: Youth; Training -- Youth -- U.S.A.; Training -- Youth -- Germany; Training -- Youth -- U.K.; Training -- Youth